Microfiltração e ultrafiltração de extrato de erva-mate (Ilex paraguariensis) - Santos, Lára Franco dos (2019)
The extract of yerba mate has properties as a natural antioxidant due to its chemical composition rich in phenolic compounds. Membrane separation processes are considered viable for the clarification and purification of plant extracts. These processes operate at low temperatures, retaining bioactive compounds, such as phenolic compounds. However, there is no literature in the literature on the stability of erva-mate extract by membranes. The objective was to develop a process by microfiltration and ultrafiltration for the clarification and stabilization of an aqueous extract of yerba mate. The parameters of time and temperature of extraction were evaluated, evaluating the best extraction condition of the phenolic compounds, the aqueous extract was submitted to clarification through three membranes: microfiltration (0.1 μm); ultrafiltration 1 (30 to 80 kDa); ultrafiltration 2 (4 kDa) and different process pressures, 0.5; 1; and 1.5 bar. The extracts obtained in the clarification stage were analyzed for the parameters of rejection, flow, turbidity, total phenolic compounds, pH, electrical conductivity, solids and total solids, color and activity of polyphenoloxidase and peroxidase enzymes. The extract of the best condition in the clarification step was subjected to a stability test for one month at different storage temperatures. The best extraction condition of the phenolic compounds was at 90 ° C for 10 minutes, high temperatures facilitate the extraction of these compounds, however it is worth noting the low stability of these compounds and how important these parameters are for the extraction stage. The turbidity values for membrane clarified permeates were below 36 NTU and there was no significant difference of the phenolic compounds from the crude extract to clarified, so any of the clarified extracts could be intended for the manufacture of beverages for example. The membrane that presented the best efficiency was that of ultrafiltration (30 to 80 kDa) at 0.5 bar, obtained a rejection of the phenolic compounds (18%), turbidity (99.9%) and kept the flow stable. The clarified extract maintained its stability for phenolic compounds and turbidity for 30 days stored at 4 ° C. The membrane separation processes were efficient in clarifying, preserving and stabilizing the phenolic compounds. This phenolic extract from yerba mate can be applied to beverages and as a substitute for synthetic antioxidants